On the identity of some endemic SW Asian Cruciferae. II - German, Dmitry A.; Özüdoğru, Bariş (Phytotaxa, 2020)
The second part of revision of the identity and status of poorly known Cruciferae species treated as local endemics within SW Asia is presented. Six taxa (Camelina alpkoyensis, Draba anatolica, Fibigia yildirimlii, Matthiola subglabra, Rorippa edirnensis, and Thlaspi kilicii) described primarily during last decade from Turkey, with the exception of M. subglabra established much earlier based on a gathering from Iran, are dealt with. All are regarded as synonyms of Camelina laxa, Draba doerfleri, Fibigia clypeata subsp. eriocarpa, Eutrema renifolium, Noccaea (Neurotropis) platycarpa, and Rorippa amphibia, respectively. Lectotypes for Draba doerfleri, D. doerfleri var. aprica, D. doerfleri var. umbrosa, and Schivereckia bornmuelleri are designated.